Spying on the Young in Depression and War: Students, Youth Groups and the RCMP, 1935-1942 - Axelrod, Paul (Labour / Le Travail, 1995)
Focusing on the experiences of the Canadian Student Assembly and the Canadian Youth Congress, this article examines the ways in which the RCMP assembled information, conducted surveillance, and interpreted the activities of student and youth "radicals" from the early 1930s to the beginning of World War II. Sources for this study include surveillance and security reports filed by RCMP informants and authorities. As well as exploring new terrain in the history of youth and higher education in Canada, this study adds to the literature on the means by which liberal democratic practices were fettered by government authorities in the depression and war years.
Keywords: CANADIAN Youth Congress; Canada; Espionage; POLICE patrol -- Surveillance operations; RADICALS; Royal Canadian Mounted Police (RCMP); STUDENT activism; YOUTH -- Political activity